Hubungan Kepemimpinan Kepala Sekolah dan Kompetensi Pedagogik Guru dengan Keinovatifan Guru - Imelda Anandiya Putri (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the relationship between Principal Leadership and Pedagogic Competence with Teacher Innovative-ness in SDN 003 Pagarsih. The method used is descriptive correlational research with a quantitative approach which consists of two independent variables, namely Principal Leadership and Pedagogic Competence and Teacher Innovativeness as the dependent variable. The number of research samples was 32 people. The research data analysis technique used statistical analysis techniques of correlation and simple regression as well as multiple correlation. This study resulted in three conclusions: First, there is a positive and very significant relationship between Principal Leadership and Teacher Innovativeness as indicated by the correlation coefficient = 0.914. Second, there is a positive and very significant relationship between Teacher Pedagogic Competence and Teacher Innovativeness as indicated by the correlation coefficient = 0.851. Third, there is a positive and very significant relationship between Principal Leadership and Teacher Pedagogic Competence together with Teacher Innovativeness as indicated by the correlation coefficient value of 0.930 and the coefficient of determination (R2) of 0.865. The results of the study indicate that teacher innovation can be increased through the pedagogical competence and leadership of the principal.